Surgical Fixation of Calcaneal Beak Fractures—Biomechanical Analysis of Different Osteosynthesis Techniques - Jordan, Martin C.; Hufnagel, Lukas; McDonogh, Miriam; Paul, Mila M.; Schmalzl, Jonas; Kupczyk, Eva; Jansen, Hendrik; Heilig, Philipp; Meffert, Rainer H.; Hoelscher-Doht, Stefanie (Frontiers in Bioengineering and Biotechnology, 2022)
The calcaneal beak fracture is a rare avulsion fracture of the tuber calcanei characterized by a solid bony fragment at the Achilles tendon insertion. Treatment usually requires osteosynthesis. However, lack of biomechanical understanding of the ideal fixation technique persists. A beak fracture was simulated in synthetic bones and assigned to five different groups of fixation: A) 6.5-mm partial threaded cannulated screws, B) 4.0-mm partial threaded cannulated screws, C) 5.0-mm headless cannulated compression screws, D) 2.3-mm locking plate, and E) 2.8-mm locking plate. Different traction force levels were applied through an Achilles tendon surrogate in a material-testing machine on all stabilized synthetic bones. Outcome measures were peak-to-peak displacement, total displacement, plastic deformation, stiffness, visual-fracture-line displacement, and mode of implant failure. The 2.3- and 2.8-mm plating groups showed a high drop-out rate at 100 N tension force and failed under higher tension levels of 200 N. The fracture fixation using 4.0-mm partial threaded screws showed a significantly higher repair strength and was able to withhold cyclic loading up to 300 N. The lowest peak-to-peak displacement and the highest load-to-failure and stiffness were provided by fracture fixation using 6.5-mm partial threaded cannulated screws or 5.0-mm headless cannulated compression screws. As anticipated, large 6.5-mm screw diameters provide the best biomechanical fixation. Surprisingly, the 5.0-mm headless cannulated compression screws yield reliable stability despite the absent screw head and washer. When such large screws cannot be applied, 4.0-mm screws also allow reasonable fixation strength. Plate fixation should be implemented with precaution and in combination with a restrictive postoperative motion protocol. Finally, clinical cases about the surgical application and recovery are included.